2021
DOI: 10.1093/ofid/ofab327
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes With Definitive Treatment of Methicillin-Resistant Staphylococcus aureus Bacteremia With Retained Daptomycin and Ceftaroline Combination Therapy vs De-escalation to Monotherapy With Vancomycin, Daptomycin, or Ceftaroline

Abstract: This retrospective single-center cohort study compared retained daptomycin and ceftaroline combination therapy versus de-escalation to vancomycin, daptomycin or ceftaroline monotherapy for MRSA bacteremia. No difference was found in the composite outcome of 60-day bacteremia recurrence, readmission or inpatient infection-related mortality for patients retained on combination therapy versus those de-escalated to monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Our findings are consistent with previously published data, suggesting that dual therapy does not provide a mortality benefit over monotherapy, after controlling for confounding factors. 10,25 However, the mean time to dual therapy initiation in our cohort was 6.1 days (SD 2.4). Considering the suggested updates to the definition of persistent bacteremia 9 , dual therapy in our cohort may have been initiated too late to provide a mortality benefit.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings are consistent with previously published data, suggesting that dual therapy does not provide a mortality benefit over monotherapy, after controlling for confounding factors. 10,25 However, the mean time to dual therapy initiation in our cohort was 6.1 days (SD 2.4). Considering the suggested updates to the definition of persistent bacteremia 9 , dual therapy in our cohort may have been initiated too late to provide a mortality benefit.…”
Section: Discussionmentioning
confidence: 74%
“…It is unknown if the median time to blood culture clearance post‐ceftaroline initiation would have been shorter if ceftaroline was added sooner. The optimal duration of using combination therapy is also unclear, but more recent data have suggested that the “second” antibiotic does not need to be continued for the entire duration 31 . Ceftaroline was continued for a median duration of 13.9 days from the first negative blood culture in our study.…”
Section: Discussionmentioning
confidence: 81%
“…The optimal duration of using combination therapy is also unclear, but more recent data have suggested that the "second" antibiotic does not need to be continued for the entire duration. 31 Ceftaroline was continued for a median duration of 13.9 days from the first negative blood culture in our study. Lastly, there are currently no large-scale, comparative data evaluating the optimal salvage regimen for persistent MRSAB.…”
Section: Discussionmentioning
confidence: 88%
“…Several clinical studies may support the efficacy of combining daptomycin with ceftaroline in the management of MRSA BSIs, IE, or PVE [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. An RCT including 40 patients randomized to combination therapy with daptomycin plus ceftaroline or to daptomycin/vancomycin monotherapy of MRSA BSIs (ICU admission up to 18%) showed that combination therapy was associated with significantly lower in-hospital mortality rate (0% vs. 26%; p = 0.029) [ 32 ].…”
Section: Targeted Treatment Of Infections Caused By Staphyl...mentioning
confidence: 99%
“…The surprising findings led the investigators to stop early the study due to an unacceptable higher risk of mortality in the monotherapy arm. Conversely, two large retrospective studies found no difference in terms of mortality rate, hospital readmission, and BSI recurrence of combination therapy with daptomycin plus ceftaroline vs. standard of care monotherapy with vancomycin, daptomycin, or ceftaroline in the treatment of MRSA BSI [ 33 , 34 ]. However, in a subgroup of patients with severe disease (median Charlson Comorbidity Index ≥ 3) and with a primary endovascular source of infection, treatment with daptomycin plus ceftaroline within 72 h from index cultures resulted in a trend toward reduced mortality rate (4.3% vs. 20.8%; p = 0.16) [ 33 ].…”
Section: Targeted Treatment Of Infections Caused By Staphyl...mentioning
confidence: 99%